Climate Change Affects Reproductive Phenology in Lianas of Australia’s Wet Tropics - Vogado, Nara O.; Engert, Jayden E.; Linde, Tore L.; Campbell, Mason J.; Laurance, William F.; Liddell, Michael J. (Frontiers in Forests and Global Change, 2022)
Lianas are increasing in abundance in many tropical forests. This increase can alter forest structure and decrease both carbon storage and tree diversity via antagonistic relationships between lianas and their host trees. Climate change is postulated as an underlying driver of increasing liana abundances, via increases in dry-season length, forest-disturbance events, and atmospheric CO2 concentrations; all factors thought to favour lianas. However, the impact of climate change on liana reproductive phenology, an underlying determinant of liana abundance, has been little studied, particularly outside of Neotropical forests. Over a 15-year period (2000 to 2014), we examined the phenological patterns of a liana community in intact rainforests of the Wet Tropics bioregion of Australia; a World Heritage Area and hotspot of floral diversity. Specifically, we assessed (1) flowering and fruiting patterns of liana species; (2) potential climate drivers of flowering and fruiting activity; and (3) the influence of El Niño-related related climatic disturbances on liana phenology. We found that flowering and fruiting of the studied liana species increased over time. Liana reproduction, moreover, rose in apparent response to higher temperatures and reduced rainfall. Finally, we found flowering and fruiting of the liana species increased following El Niño events. These results suggest that liana reproduction and abundance are likely to increase under predicted future climate regimes, with potentially important impacts on the survival, growth, and reproduction of resident trees and thus the overall health of Australian tropical rainforests.